Vocabulary strategies to enhance the development of oral skills of 8th grade students at “Bernardo Valdivieso” high school (morning section) in Loja. academic year 2013 – 2014 - Conza Armijos, Hover Ismael (2015)
On this descriptive research, the effectiveness of the vocabulary strategies used by EFL teachers over the development of oral skills of eight grade students at Bernardo Valdivieso high school was analyzed. The researcher elaborated a questionnaire that was applied to both teachers and students. The results became the evidence to determine which strategies students were most familiar with, the most effective at the moment of learning and assessing vocabulary acquisition, and the ones with higher effect over listening and speaking. The results indicated that teachers and students recognize the direct relationship between the use of vocabulary strategies and students’ development of oral skills. Strategies such as illustrations, challenges and word classifications indeed boost the development of listening and speaking, therefore it is imperative for teachers to use them regularly. By doing so, students will improve the quality of their communicative skills and will certainly become proficient language users.